The role of the Open Balkans in current regional relations from the strategic policy and European integrations perspective - Arnaudov, Mitko (Napredak, 2023)
Economically-oriented regional initiatives are not new phenomena in interstate relations. Most of these initiatives were aimed at promoting and dynamizing economic developments in the region, thus dynamizing the national economies of the participating actors, bearing in mind the fact that economic cooperation between political entities in the immediate region greatly contributes to the development of the national economy and market precisely because of logistical possibilities, today extremely important in regional, as well as in international economic trends. The aim of this paper is to analyze the existing achievements within the framework of the Open Balkans initiative, its capacities and possibilities, but also its results at the regional level as well as in the context of the European integration of the region. Accordingly, the main research question that arises for us in this paper is whether the Open Balkans, as an economic initiative, can contribute in strategic terms to better foreign policy positioning of Serbia and the participating countries. Theoretically speaking, the importance of this paper lies in the analysis of the role of small and micro countries in regional relations and in the process of European integration, which in certain circumstances act jointly through regional initiatives, as well as in the answer to the question of how much such initiatives contribute to the more efficient and effective realization of the foreign policy goals of small and micro entities.
Keywords: regional integration; Open Balkans; economic integration; European integration; strategic importance